Analogi Mitos “Weri Ata” dan Kurban Salib Kristus untuk Mencari dan Menemukan Profil Agen Pastoral yang Berciri Dedikatif dan Inovatif - Marselus Kur (Jurnal Alternatif Wacana Ilmiah Interkultural, 2012)
The studyand the process of Inculturation is a pastoral imperative in the Church. There are principles how to guide the process of Inculturation among others that Inculturation presupposes indeed the Cultural Intelligence with all its aspects or elements. The knowledge about cultural contexts and at the sametime about the richness of the Gospel that has been never cultural free in the history of the Church is a core necessity for the Church.This article is dealing a lot with this process of Inculturation, a dialogue between local heritage called “Weri Ata" and the mistery of the Christian Sacrifice of the Cross. It has been a narration of commitment, self-offering, social wisdom, solidarity with others, liberation, symbol of incarnation of Christ in a certain culture, harmony and disharmony, dialogue between God and mandkind in the course of the history of the people. The article has shown repeatedly about the role of “analogical imagination" that has been acknowledged in order to be able to responsibly go ahead with the process of Inculturation.